Aposynagōgos and the historical Jesus in John : rethinking the historicity of the Johannine expulsion passages - Bernier, Jonathan. (Biblical Interpretation Series, 2013)
In Aposynagōgos and the Historical Jesus in John , Jonathan Bernier utilizes the critical-realist hermeneutics developed by Bernard Lonergan and Ben F. Meyer to survey historical data relevant to the Johannine expulsion passages (John 9:22, 12:42, 16:2). He evaluates the major two contemporary interpretative traditions regarding these passages, namely that they describe not events of Jesus' lifetime but rather the implementation of the Birkat ha-Minim in the first first-century, or that they describe not historical events at all but serve only to construct Johannine identity. Against both traditions Bernier argues that these passages plausibly describe events that could have happened during Jesus' lifetime.